Analyzing Teachers’ Needs for Digital-Based Collaborative Training Toward Quality Inclusive Education - Bastiana, Bastiana; Syamsuddin, Syamsuddin; Maenuddin Bustanil Syah; Reza Hadiwijaya Dynasti (Indonesian Journal of Learning Education and Counseling, 2026)
Inclusive education requires effective collaboration between regular teachers and special education teachers to ensure equitable learning opportunities for all students. Although teacher collaboration has been widely discussed in inclusive education literature, limited research has examined teachers’ needs for digital-based collaborative training that supports structured collaboration through digital technology. In many inclusive schools, collaborative practices are still constrained by limited digital competence and the lack of systematic professional development programs. This study aims to analyze teachers’ needs for digital-based collaborative training in inclusive education settings as a preliminary needs analysis for developing a collaborative training model.  The study employed a quantitative descriptive design involving 20 teachers from inclusive schools in Makassar, consisting of 10 special education teachers and 10 regular teachers, selected using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistical analysis (percentage) to identify the level and dimensions of teachers’ training needs. The findings indicate that teachers demonstrate a high need for strengthening digital literacy to support collaborative practices, particularly in the use of educational technology for communication, joint lesson planning, and instructional coordination between teachers. Teachers also report a strong need to improve collaborative competencies and develop structured strategies for implementing collaborative learning in inclusive classrooms. These findings provide empirical evidence for determining teachers’ professional development priorities and contribute to the development of digital-based collaborative training models that strengthen teachers’ digital competence and support more effective collaborative practices in inclusive education.